Leslie Barnes. Vietnam and the Colonial Condition of French Literature. Lincoln: U of Nebraska P, 2014. - Michele L. Gerring (Studies in 20th & 21st Century Literature, 2017)
Review of Leslie Barnes. Vietnam and the Colonial Condition of French Literature. Lincoln: U of Nebraska Press, 2014.
Keywords: vietnam; colonialism; French literature